Enlightenment on unani concept of ghiza (Diet) In modern perspective - Fahamiya, N.; Shiffa, M.S.M.; Farzana, M.U.Z.N. (World Journal of Pharmaceutical and Life Sciences, 2016)
Unani healing system employs a holistic approach in prevention and treatment of diseases. This system of medicine emphasizes six essentials pre-requisites (Asbab-e- Sitta-e- Zarooriya) that have been laid down for the promotion of health and prevention of disease. Among them food is one of the pre-requisites. Ancient Unani physicians gave much importance to diet in both health and disease. In recent years, public awareness of health benefits of functional food and nutraceuticals has been expanded in prevention of risk of developing diseases and improvement in overall health. Therefore, there is a need for solid information on functional food and nutraceuticals to better inform health professionals and the public about these foods. This literary research is aimed to give enlightenment on Unani concept of Ghiza (Diet) with special reference to its nutraceuticals and functional perspective. Data was gathered from Unani classical texts, scientific journals and internet. The gathered data was analyzed and the results showed that the terminology and definitions for nutraceuticals/functional foods are inconsistent worldwide, and there are no international standards for regulation of nutraceuticals/functional foods to serve as baselines. However, the Unani medicine has given a clear idea on classification and role of food which could be enlighten the modern terms nutraceuticals and functional foods for the better utilization in both health and disease.
Keywords: Functional food; nutraceuticals; Ghiza; Asbab-e-Sitta-e-Zaroriayah